THE DEVELOPMENT OF ENGLISH FOR TRANSPORTATION (ENTRA) APPLICATION FOR STUDENTS IN TRAINING AND EDUCATION PROGRAM FOR HUMAN RESOURCE DEVELOPMENT ON TRANSPORTATION AGENCY - Munawwir Hadiwijaya; Ima Widiayanah; Maya Rizki Amalyasari (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2019)
This research seeks to develop an English for Transportation (EnTra) application that can help cadets to master English transportation more easily. The design of this research is the ADDIE model development research. The following steps describe the research and development. (1). Conduct a needs analysis through preliminary research activities. (2). Planning in the form of product and participant determination. (3). The product to be developed is the English for Transportation (EnTra) application. (4). Expert validation in the form of expert / practitioner ratings of the Entra application includes format, language, illustrations and content, as well as multimedia experts, because the product produced is an android application. (5). Implementation of the product to the real target. (6) Product evaluation. The results of this study indicate that, the application developed has been tested and validated by experts and categorized very qualified, with detailed results as follows: Material experts with an average of 4.55 or 90.91%, media experts with a mean of 4.31 or 86.26%, and cadets with an average of 4.03 or 80.53%.